Differential diagnosis of the multiple focal lesions and expansive process of brain in early stage of the disease - V. V. Fonin; I. A. Gribachyova; A. P. Dergilev (Бюллетень сибирской медицины)
Differential diagnosis of the multiple focal lesions and expansive process of brain was conducted in 78 patient in early stage of the disease when it was mono symptom clinic. Only MRI helped to make the proper decision.